2008
DOI: 10.1246/cl.2008.1300
|View full text |Cite
|
Sign up to set email alerts
|

Neopentyl-substituted PNP-pincer Ligand: Complexation with Iridium to Form an Iridacycle via Alkyl C–H Activation

Abstract: A new PNP-pincer ligand 1 bearing neopentyl substituents reacted with [Ir(cod)2]BF4 to form hydridoiridacycle 3 via oxidative addition of a C–H bond of a neopentyl group to IrI. Addition of π-acceptor ligands induced C–H reductive elimination to form cationic iridium(I) complexes 5 ligated by the π-acceptor ligand. Although 3 did not give a benzene adduct, reaction of 3 with nitrobenzene or acetophenone afforded the C–H activated 7a or 8a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Therefore, the u-geometry is usually favored in pincer-like complexes, but recently a few examples with the unusual ip-geometry have been reported. [53][54][55] Complex [7] + is slightly less sterically congested compared to [5] + -endo. VT 1 H NMR studies revealed a reduced Cp 0 -rotation barrier of DG z (200 K) = 8.9 kcal mol À1 .…”
Section: Catalytic Transfer Hydrogenation Activitymentioning
confidence: 99%
“…Therefore, the u-geometry is usually favored in pincer-like complexes, but recently a few examples with the unusual ip-geometry have been reported. [53][54][55] Complex [7] + is slightly less sterically congested compared to [5] + -endo. VT 1 H NMR studies revealed a reduced Cp 0 -rotation barrier of DG z (200 K) = 8.9 kcal mol À1 .…”
Section: Catalytic Transfer Hydrogenation Activitymentioning
confidence: 99%
“…One can expect that the narrow space around the metal center due to the bulky substituents may suppress the reactivities of metal-hydrogen and metal-X bonds (X = C, N, and O). Therefore, we recently have reported design and synthesis of neopentyl-substituted PNP-pincer ligand 1 possessing remote steric bulkiness far away from the metal center [34]. Complexation of 1 with iridium complex afforded an iridacycle 2 with a cleavage of neopentyl C-H bond (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Substituents on such ligands span a wide range of electronic and steric properties, from electron-withdrawing C 6 F 5 groups through to bulky and electron-donating neopentyl groups. 75,76 This work aimed to investigate the synthesis, properties, and catalytic activity of rhodium and iridium complexes bearing "cooperative" pincer ligands. The PCNCP framework * was selected due to the ability of the backbone to undergo dearomatisation when deprotonated at the methylene positions (see chapter one).…”
Section: Ligand Synthesismentioning
confidence: 99%
“…For example, when the neopentyl-substituted ligand t BuCH 2 PNP is reacted with [Ir(cod)(µ-Cl)] 2 , the chelating cod ligand is displaced and one of the t Bu groups is metallated (Figure 4.1-A). 76 In the case of Ph PNP, the cationic η 4 -cod complex is formed (Figure 4.1-B). This complex is able to hydrogenate imines.…”
Section: Iridium Complexesmentioning
confidence: 99%
See 1 more Smart Citation